Arsenic behavior in the autoclave-hydrometallurgical processing of refractory sulfide gold-platinum-bearing products - V. Petrov, G; B. Fokina, S; Y. Boduen, A; E. Zotova, I; F. Fidarov, B (International Journal of Engineering and Technology, 2018)
Among various types of gold-bearing ores a special place belongs to the ores, which contain gold finely-dispersed in sulphide minerals, mostly in arseno-pyrite and pyrite. Autoclave-hydrometallurgical processing technologies for such raw materials seem to be of a particular interest for study. However, autoclave oxidation of sulfide-arsenic material results in significant amounts of technological solutions with high concentrations of arsenic, iron and sulfuric acid.This article represents the studies of how arsenic behaves in autoclave oxidative leaching of a refractory sulphide gold-platinum-bearing concentrate. We studied how the composition of arsenic-bearing solutions in autoclave leaching (acidity, concentration of iron and arsenic) influences the depth of arsenic precipitation when neutralized with calcium-containing reagents, which allows converting the maximum amount of arsenic together with iron in the form of iron arsenate into a stable long-term storable precipitation.